2008
DOI: 10.1053/j.gastro.2007.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Dose and Duration of Use and Risk of Colorectal Cancer in Men

Abstract: Background and Aims-Long-term data on the risk of colorectal cancer according to dose, duration, and consistency of aspirin therapy are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
210
4
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 223 publications
(233 citation statements)
references
References 55 publications
13
210
4
6
Order By: Relevance
“…There is plausible evidence that chronic inflammation plays an etiologic role in colorectal carcinogenesis, as it has been consistently observed that individuals with chronic inflammatory bowel diseases have a higher risk of colorectal cancer [79,80]. In addition, the use of aspirin and other anti-inflammatory drugs has been associated with a lower risk of colorectal cancer, which gives further support for a role of inflammation in colorectal carcinogenesis [81][82][83][84]. Obesity-associated chronic low-grade inflammation [4] may play an important role in colorectal carcinogenesis through fostering cell proliferation, cell survival and migration [85].…”
Section: Inflammatory Markersmentioning
confidence: 92%
“…There is plausible evidence that chronic inflammation plays an etiologic role in colorectal carcinogenesis, as it has been consistently observed that individuals with chronic inflammatory bowel diseases have a higher risk of colorectal cancer [79,80]. In addition, the use of aspirin and other anti-inflammatory drugs has been associated with a lower risk of colorectal cancer, which gives further support for a role of inflammation in colorectal carcinogenesis [81][82][83][84]. Obesity-associated chronic low-grade inflammation [4] may play an important role in colorectal carcinogenesis through fostering cell proliferation, cell survival and migration [85].…”
Section: Inflammatory Markersmentioning
confidence: 92%
“…An analysis of 662424 men and women enrolled in the Cancer Prevention Study Ⅱ cohort showed that daily use of aspirin for at least 5 years was associated with a 32% reduction in risk of CRC [9] . Two cohort studies of United States health professionals (47363 men and 82911 women) showed that regular aspirin users (≥ 2 times/wk) had 21% and 23% lower risk of CRC, respectively, during follow-up periods of 18 and 20 years respectively [10,11] . Moreover, in a separate analysis of a Nurses Health Study cohort, regular aspirin use also reduced the risk of death from CRC by 28% and risk of death from any type of cancer by 12% [12] .…”
Section: Clinical Effects Of Aspirin On Sporadic Crcmentioning
confidence: 99%
“…Some suggested that 300-325 mg may be necessary for CRC prevention but most provided incomplete information regarding the dose and duration of aspirin treatment [7,8,10,11,27] . Therefore, taking the clinical trial and observational information together, there is very strong evidence that long-term LDA (75-325 mg/d) reduces the risk of CRC.…”
Section: Ppi Usementioning
confidence: 99%
“…[75][76][77] Multiple prospective observational studies have demonstrated an association between aspirin use and decreased CRC mortality. [78][79][80] Data on aspirin as a treatment for CRC (postdiagnosis usage) are more limited and drawn only from observational studies. Domingo et al 81 and Liao et al 82 found a survival advantage for posttreatment aspirin users only in patients whose tumors exhibit PIK3CA mutations; however, a recent cohort study did not validate these observations.…”
mentioning
confidence: 99%